Kaili traditional classification: the customs influence on Kaili Kingdom’s authority in Palu Valley (Research, Society and Development, 2023)
This article aims to analyze the influence of adat on the sustainability of the patanggota system in Kaili Land. This article focuses on the traditional classification of the Kaili people in the Palu Valley who adhere to the patanggota system, namely the kingdoms of Tavaeli, Palu and Tatanga. This research was conducted using historical methodology through an anthropological approach. The main sources of this research are royal documents, while the secondary sources are journals and books made by local Kaili humanists, as well as interviews with traditional leaders and Kaili nobility. These sources are criticized and interpreted, then written in the form of research articles. This article discusses the assumption that the principles of traditional Kaili society are static, especially the cultural values ​​of leadership in the kingdom, as expressed by local culturalists from the perspective of cultural anthropology such as Suaib Djafar, Masyhuddin Masyhuda, and Jaruddin Abdullah. Meanwhile, other local humanists such as Mattulada and Haliadi who focus on the perspective of cultural history state that these principles are already dynamic because they accept new changes.